دوافع تعرض المراهقين لبرامج اكتشاف المواهب ببعض قنوات التليفزيون المصري والإشباعات المتحققة منه - الطنباري، فاتن عبدالرحمن; متولي، إيمان محمد عبدالقوي; شلبي، أشرف مصطفى أحمد (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2018)
الهدف: هدفت الدراسة إلى التعرف على دوافع وأسباب تعرض المراهقين لبرامج اكتشاف المواهب بالتليفزيون المصري. العينة: تتمثل عينة الدراسة الميدانية من الشباب الجامعي المصري من طلاب الفرقة الأولى، وتم اختيار عينة الدراسة وفقا لأسلوب العينة العمدية من متابعي برامج اكتشاف المواهب بالتليفزيون المصري، وأجريت الدراسة على عينة قوامها 300 مفردة من الطلاب (ذكور، إناث) من محافظة القاهرة والجيزة، تمثل التوزيع المتساوي على الجامعات المصرية الحكومية والخاصة، جامعة حكومية 150 وطبقت على جامعة عين شمس، جامعة خاصة 150 وطبقت على جامعة 6 أكتوبر. النوع والمنهج: تنتمي هذه الدراسة إلى الدراسات الوصفية، والتي تستخدم منهج المسح الإعلامي بالعينة. الأدوات: استمارة الاستبيان لتطبيق الدراسة الميدانية على عينة من المراهقين. النتائج: جاء في الترتيب الأول من حيث البرامج المفضلة برامج المسابقات واكتشاف المواهب بنسبة بلغت 47.0%، بينما جاء في الترتيب الأول من حيث أهم البرامج مشاهدة برنامج Arab Idol بنسبة بلغت 40.5%، قد جاء في الترتيب الأول لدوافع المشاهدة للمتعة والترفيه بنسبة بلغت 47.3%، بينما من يعتقدون أن برامج اكتشاف المواهب تسهم في اكتشاف مواهبهم جاءوا بنسبة بلغت 42.9%، في حين جاء في الترتيب الأول مسابقات لحفظ القرآن الكريم بنسبة بلغت 73.0%، جاءت نسبة من يرون برامج اكتشاف المواهب بالفضائيات العربية متنفسا في الهروب من أخبار السياسة من إجمالي مفردات عينة الدراسة بلغت 52.4%، أكدت نتائج الدراسة علي أن نسبة من يرون برامج اكتشاف المواهب بالفضائيات العربية تقدم مواهب حقيقية من إجمالي مفردات عينة الدراسة بلغت 48.2%.
Aims: The study aimed to: knowing the motives and reasons for the teenagers exposure to talent discovery programs in some Egyptians television channels and gratifications achieved from it. Sample: The sample of field study represented in the university Egyptian young of the students of the first class, the study sample was chosen according to the method of sample from followers of discovers talent in some Egyptians television channels, this study was conducted on 300 sample of students either female or male from Cairo and Giza, the equal distribution on the Egyptian public and private universities, It was applied to 150 from Ain Shams University a public university, and applied to 150 from October 6 university a private university. Type: Methodology: This study belongs to descriptive studies, which use media survey methodology in the sample. Tools: Questionnaire for applying the field study to a sample of teenagers Results: Competition programs and talent discovery Come in the first rank in term of favorite shows a rate of 47.0%, when come in the first rank in term of The most important view programs “Arab Idol” a rate of 40.5% in the first rank has come the motives for viewing "entertainment and leisure" a rate of 47.3%, while some of people believe that talent discovery programs contribute to the discovery of their talents at a rate of 42.9%, while in the first rank ’'competitions for memorizing the Holy Quran" by 73.0%, the percentage of those who see the talent discovery programs in some Egyptians television channels is a flight from politics news from the total sample of the study sample reached 52.4%, The results of the study confirmed that the percentage of those who see talent discovery programs in some Egyptians television channels offers real talents of the total items of the study sample reached 48.2%.
Keywords: المراهقين -- الشباب الجامعي -- البرامج التلفزيونية -- برامج إكتشاف المواهب -- التليفزيون المصري